The role of proximity in foreclosure externalities: Evidence from condominiums - Lynn M. Fisher; Lauren Lambie-Hanson; Paul S. Willen (Federal Reserve Bank of Boston, 2013)
We explore several different explanations of the effect of foreclosures on neighboring properties using a dataset of transactions in Boston, for which we have rich data on the size and location of condominium associations. There is compelling evidence against a supply effect-nearby condo foreclosures in different associations, and even those within the same association but at different physical addresses, have little impact on condo sale prices. However, condos transact at average discounts of 2.4 percent when a foreclosure shares the same physical address. We view the results as indicating that investment externalities drive foreclosures' impacts on neighboring house prices.
Keywords: G21; K11; R31; 330